Van-der-Waals-gap tunneling spectroscopy for single-wall carbon nanotubes. (March 2017) - Choi, Dong-Hwan; Jang, Seunghun; Jeong, Du-Won; Lee, Jeong-O; Chang, Hyunju; Ha, Dong-Han; Lee, Seung Mi; Kim, Jongwoo; Suh, Yung Doug; Bae, Myung-Ho; Kim, Ju-Jin
Abstract: As a consequence of their unique electronic band structures, low-dimensional materials such as one-dimensional (1D) single-wall carbon nanotubes (SWCNTs), 2D graphene and various 2D transition-metal dichalcogenides have exhibited intriguing electrical transport properties when incorporated into field-effect transistors. Meanwhile, the van-der-Waals (vdW) interfaces between top-contacted metals and low-dimensional materials have become a challenging issue for future high-performance electronics. Here, we report a new aspect of vdW interface that offers vdW-gap tunneling spectroscopy by adopting indium (In) as a top-contacted metal on SWCNTs without an artificial insulating tunnel barrier. We show that multiple differential conductance peaks for varying bias voltages correspond to the van Hove singularities existing in the electronic density of states of SWCNTs. Our first-principles calculations reveal that In forms a physisorption interface with a considerable vdW gap, which causes little disruption to the density of states of the SWCNTs near the metal interface and which thus allows vdW-gap tunneling spectroscopy. Graphical abstract: